2009
DOI: 10.1589/jpts.21.129
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Center of Pressure during Stair Descent in Young and Healthy Elderly Adults

Abstract: Abstract.[Purpose]The purpose of this study was to investigate the center of pressure (COP) trajectory during stair descent in young and healthy elderly adults.[Subjects] Fifteen community-dwelling healthy elderly adults (mean age, 73.1 ± 4.3 years) and 15 healthy young adults (mean age, 23.6 ± 2.4 years) volunteered to participate in this study.[Methods] Subjects stood in a predetermined position on the top of a staircase. Participants were then instructed to descend the staircase with three steps at a self-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…In previous studies, Chris et al 33) and Kim 34) have demonstrated increased backward movement of the COP after Tai Chi training in fallprone adults. Interestingly, TC participants were able to increase the magnitude of the A-P displacement of the COP closer to the magnitude reported for more healthy elderly subjects 52) , whereas WE participants showed little change in the displacement of the A-P COP.…”
Section: Discussionsupporting
confidence: 64%
“…In previous studies, Chris et al 33) and Kim 34) have demonstrated increased backward movement of the COP after Tai Chi training in fallprone adults. Interestingly, TC participants were able to increase the magnitude of the A-P displacement of the COP closer to the magnitude reported for more healthy elderly subjects 52) , whereas WE participants showed little change in the displacement of the A-P COP.…”
Section: Discussionsupporting
confidence: 64%
“…Dynamic stability during gait is the ability to control one's centre of mass (COM) within a moving base of support [10][11][12]. Centre of pressure (COP) has been defined as the neuromuscular response to shifts in the body's COM and measures of COP have been used as an indicator of dynamic stability [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Centre of pressure (COP) has been defined as the neuromuscular response to shifts in the body's COM and measures of COP have been used as an indicator of dynamic stability [10,12]. Previous studies have quantified displacement of the COM and COM-COP separation during level walking [13] and stair ambulation [11,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations